SVART ARBETE, VITT ARBETE: Hur lite skit i hörnen blev ett rent helvete - Larsen, Lotta Björklund (Tidsskriftet Antropologi, 2005)
The article discusses a case which made the headlines of Swedish newspapers in the spring of 2003. A group of suburban women was caught using an immigrant woman without work permit to clean their homes. The indictments read “crimes against the aliens act”, but the debate focused on svart arbete, literally translated as black market work or moonlighting. Both svart arbete and paid home-cleaning contribute to an infected debate with political undertones in Swedish society. The article makes an analysis of the women’s justifications and explanations of their use of domestic cleaning services in the context of changes currently underway in Swedish society. The welfare state and its institutions are adapting to EU-membership and an enlarged labour market. Individual actors, both providers and buyers, respond to these market possibilities in different ways. Ethical and economic considerations are examined vis-à-vis these women’s own employment, and in regard to perceived earning possibilities for the foreign cleaning woman. Different conceptions of formal and informal work in the domestic sphere are discussed.